Antimicrobial Resistance of Invasive Pneumococci in Finland in 1999-2000 - Pihlajamäki, Marja (American Society for Microbiology, 2003)
The resistance patterns and macrolide resistance mechanisms of 910 Finnish invasive pneumococci isolated during 1999 and 2000 were studied. Macrolide resistance was detected in 6.9% of isolates. Penicillin resistance was detected in 1.5% of isolates, and penicillin intermediate resistance was detected in 4.0% of isolates. Active macrolide efflux, mediated by the mef(A) gene, was the most common macrolide resistance mechanism. Four macrolide-resistant isolates had mutations in rRNA or ribosomal protein L22.